Factors Affecting the Surgical Outcome in Extradural Hematoma in Punjab Institute of Neurosciences, Lahore, Pakistan - Niaz, Azam; Nasir, Muhammad Hammad; Niraula, Kiran; Majeed, Sumra; Neupane, Joshan; Ghimire, Megha; Vohra, Anjum Habib (Nepal Journal of Neuroscience, 2017)
Head injury is a leading cause of death in young age group. Extra Dural hematoma, a complication of head injury, is often fatal if not treated in time. The surgical outcome of EDH is dependent upon many variables including preoperative GCS, time between injury and surgery, associated intracranial injuries, anisocoria and hematoma volume. In order to reduce the mortality near to nil, it is essential to determine the magnitude of effect of affecting factors on surgical outcome which will also help us in preoperative counseling and prioritizing the operative candidates. This study was conducted determine the factors affecting surgical outcome of traumatic intracranial extradural Hematoma in Punjab Institute of Neurosciences/ Lahore general hospital, Lahore. It was a Cross sectional study conducted for 3 years from 28th May 2012 to 28th May 2015.The study was conducted on the patients admitted through emergency and diagnosed as Extramural hematoma. These patients underwent surgical evacuation of EDH on emergent basis and outcome was measured by Glasgow Outcome Scale (GOS) after 48 hours of surgery. Using GOS, good surgical outcome was observed in 80.9% (157 out of 194) patients. Preoperative GCS, anisocoria, hematoma volume, associated intracranial injuries and time between injury and surgery were the factors affecting the outcome significantly (p value=0.000) while age and sex of the patient had no significant effect. In Conclusion, good surgical outcome is associated with patients with solitary Extra Dural Hematoma of volume less than 60 ml, preoperative GCS more than 8, absence of anisocoria and undergoing surgical evacuation within 6 hours of injury. Nepal Journal of Neuroscience, Volume 14, Number 3, 2017, Page: 13-18